Associations between relapse and drinking behaviors in patients with alcohol use disorders: A 6‐month prospective study - Kazuhiro Kurihara; Hotaka Shinzato; Yoshikazu Takaesu; Tsuyoshi Kondo (Wiley, 2023)
Abstract Background Habitual behaviors, rather than goal‐oriented behaviors, mainly characterize drinking patterns in patients with alcohol use disorder (AUD). However, few studies have focused on the influence of drinking behavior on AUD relapse. This prospective study examined associations between drinking behavior patterns and alcohol‐use relapse using the 20‐item questionnaire for drinking behavior patterns (DBP‐20). Methods We enrolled patients with AUD and compared the cohort's demographic data and 6‐month outcomes based on the DBP‐20 and the Alcohol Use Disorders Identification Test between two groups (alcohol use relapse vs. abstinence). We also assessed the results for significant factors related to relapse. Results We included 105 patients with AUD. More patients in the relapse group (n = 63) were active smokers and lived alone, while fewer took medication with cyanamide or disulfiram than those in the abstinence group (n = 42). The DBP‐20 automaticity subscale score was higher in the relapse group than that in the abstinence group. Current smoker, living alone, and automatic drinking habits were significantly associated with AUD relapse. Conclusions Automaticity may be a risky drinking behavior that leads to future relapse in patients with AUD, justifying behavioral strategies to combat automatic drinking for relapse prevention.